MULTICHANNEL ANALYSIS OF THE REACTION K-P-]K-BAR-O-PI-P AT 4.2 GEV-C - Engelen, J; Heinen, P; Kittel, E; Metzger, W; Schotanus, D; Vergeest, J; Zralek, M; Jongejans, B; Massaro, G; Dionisi, C; Ferrando, A; Gavillet, P; et al. (1980)
An analysis is presented of the reaction K-p→K0π-p at 4.2 GeV/c incident momentum, using analytical techniques in fully dimensional phase space. This methods allows to isolate the contributions of the 0+, 1- and 2+ (Kπ) partial waves in various helecity Separating well-understood contributions from the rest, the method is particularly useful for the detection of small effects (≈1% of the total final-state cross section) not visible in the mass distributions: (i) small cross-section contributions of 3- (Kπ partial waves, K*(1780), are unambiguously isolated; (ii) 3.5σ evidence is given for Σ(1480) in the (pK0) system; (iii) effects due to a second Kπ P-wave or the possible presence of a doubly peripheral mechanism are discussed. The method furthermore allows simultaneous treatment of the (Kπ) partial waves, pπ) partial waves and their interferences and of a Σ(1765) signal (with spin 5 2). While interferences within the (Kπ) and within the (pπ) systems are strongly determining the corresponding distributions, no interference between these systems is needed. © 1980.